The Potential Healing Properties of Systemic Probiotic-Prebiotic Supplement on Angular Cheilitis - Malath Nabil Jafar (Journal of Global Pharma Technology, 2020)
Background: Angular Cheilitis frequently caused by anemia and malnutrition such as iron, B12, folate and zinc deffiency, but can also be caused by fungi. Probiotics are live organisms thought to benefit human health. Aim of the study: to test the efficacy of probiotics in the healing process of angular Cheilitis in elderly individuals. Materials & Methods: The sample included 58 individuals (both genders) with clinically apparent angular Cheilitis. The duration of the disease was between 8-10 days. The age ranged between (55-65) years. Probiotic-prebiotic food supplement selected to be used is (max biotic XL) sachets. Results: the majority of recovery cases recorded during the 2nd week in both genders, females showed better response as compared to males. The recovery potential declines with age. Conclusion: The main conclusions that have obtained in this research that the treatment is effective 89.5% for both genders. And it is more effective for females than males, the healing time for most patients is two weeks, and the treatment is more effective on age 60 for both genders. Keywords: Probiotics, Prebiotics, Cheillitis, Supplement, Healing.